Incidence of active pulmonary tuberculosis in patients with coincident filarial and/or intestinal helminth infections followed longitudinally in South India. - Soumya Chatterjee; Chockalingam Kolappan; Rangasamy Subramani; Punnathanathu G Gopi; Vedhachalam Chandrasekaran; Michael P Fay; Subash Babu; Vasanthapuram Kumaraswami; Thomas B Nutman (PLoS ONE)
Background Filarial (and other helminth) infections are known to modulate mycobacteria-specific pro-inflammatory cytokine responses necessary for maintaining latency in tuberculosis (TB). We sought to address whether helminth co-infection alters progression to active pulmonary TB in a co-endemic area of South India. Methods/principal findings Incidence of active pulmonary TB was assessed in 5096 subjects from five villages among helminth-infected (hel⁺) and -uninfected (hel⁻) groups. Baseline stool examinations, circulating filarial antigen, and tuberculin skin testing (PPD) were performed along with chest radiographs, sputum microscopy, and culture. During three follow-up visits each 2.5 years, patients were assessed using PPD tests and questionnaires and--for those with potential symptoms of TB--sputum microscopy and culture. Of the 5096 subjects, 1923 were found to be hel⁺ and 3173 were hel⁻. Follow up interval stool examination could not be performed. In each group, 21 developed active TB over the course of the study. After adjusting for sex, age, BCG vaccination status, and PPD positivity, no difference was seen in active TB incidence between hel⁺ and hel- groups either at baseline (relative risk (RR) 1.60; 95% confidence interval (CI): 0.69, 3.71, P = 0·27), or when followed prospectively (RR 1.24; 95% CI: 0.48, 3.18, P = 0·66). Conclusions/significance Our findings suggest that, despite the immunomodulatory effects of helminth infection, baseline co-morbid infection with these parasites had little effect on the clinical progression from latent to active pulmonary TB.